Translocator Protein (TSPO) - Nunzio Denora (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The high number of papers submitted and ultimately accepted for publication in this special issue attests the great amount of research being conducted on TSPO and its role in living cells. Thus, TSPO has become an extremely attractive subcellular biomark for the early detection of disease states overexpressing this protein and for the selective delivery to mitochondria of drugs and probes. Moreover, the effort in the design and synthesis of new, more specific and effective TSPO ligands proves to be very valuable. All these topics have been addressed in the special issue.